Hak dan Kewajiban dalam Jaminan Resi Gudang : Kajian terhadap Aspek Kepastian Hukum dan Risiko bagi Kreditur - Ardian Yoan Reno Hariawan; Aisyah Fashonia; Ach Made Anthony Sanjaya; Maulidatul Hasanah (Lembaga Pengembangan Kinerja Dosen, 2025)
Warehouse Receipt is an alternative financing instrument that enables farmers and agribusiness actors to access capital by using stored commodities in licensed warehouses as collateral. This mechanism not only addresses the limited access to financing in the agricultural sector but also functions as a risk mitigation tool against commodity price fluctuations. In Indonesia, the implementation of the Warehouse Receipt System is legally regulated and supported by institutions such as the Commodity Futures Trading Regulatory Agency (Bappebti) and PT Kliring Berjangka Indonesia. However, its effectiveness still faces several challenges, including low financial literacy among farmers, limited warehouse infrastructure, and suboptimal inter-agency coordination. Therefore, policy strengthening, increased public awareness, and digital system development are essential to optimize the role of Warehouse Receipts in enhancing the agricultural sector and maintaining commodity price stability.